Pedagogical changes towards the implementation of the Bologna Process: indicators’ structure of measurement - Ramos, A. (2013)
The transition into the twenty-first century brought about important changes in society, including the areas of education and teaching. The establishment of the European Higher Education Area represents an effort to face these changes together in Europe. The changes in the teaching and learning models in higher education led to the institutional promotion of extensive interventions in order to alter the status quo that has prevailed for decades. The need for a cultural renewal of the teaching staff involved in higher education, attending to the centrality of student’s learning rather than knowledge per se, is also a challenge to be overcome. This study intends to highlight the central elements concerning the Bologna Process and the topics connecting the objec- tives and their intrinsic principles. This initial approach is the basis for the design of a proposal for monitoring the implementation of the Bologna Process in an institution of higher education in Portugal. The results suggest a proposal consistent with the needs in terms of monitoring the implementation of the Bologna Process. This proposal allows, in addition to static analysis relative to a specific academic year, dynamic analysis between academic years, uncovering best practices and areas for improvement.